Mengurai Tradisi Brandu dan Penularan Antraks sebagai Strategi Eliminasi Wabah Antraks di Gunungkidul, Yogyakarta - Firdaus, Allama Rozan; Hasna, Ratih Aulia; Putri, Luluk Kiesa; Kriswardhani, Pamula Nur; Zidan, Muhammad Hafidz; Triratnawati, Atik (Universitas Padjadjaran, 2024)
Gunungkidul is one of the livestock-producing regions in Indonesia. Anthrax poses a significant threat to both livestock health and human well-being in the area. Various risk factors contribute to Anthrax transmission, including sociocultural factors, especially the Brandu Tradition. Brandu is a tradition in Gunungkidul where a group of community members collect funds to buy dead or sick cattle (usually cows) owned by one of the community members, at a meager price. The funds then were given to the cattle owner as a collective support for losing his cattle. The sick or dead cattle being slaughtered and the meat were distributed among the community members who participate in the funding. The tradition of distributing dead cattle meat has significantly contributed to the spread of zoonoses diseases, including Anthrax. This research aims to analyze the factors that underpin the Brandu tradition; to explore the role of this tradition in spreading Anthrax; as well as to propose an appropriate recommendation for the strategy to eliminate the Brandu tradition in Gunungkidul which fits within the local socio-cultural context. This research applies a qualitative ethnography approach. Findings of this research suggest that lack of knowledge about Anthrax disease as well as some socio-cultural, psychological, and economic factors underpin the Brandu tradition. However, other traditions of collecting funds, such as Jimpitan, to relieve economic burden due to cattle loss could be promoted to gradually replace the tradition of slaughtering sick or dead cattle.